Modelling the impact of household life cycle on slums in Bangalore. (July 2017) - Roy, Debraj; Lees, Michael Harold; Pfeffer, Karin; Sloot, Peter M.A.
Abstract: According to the United Nations Human Settlements Program (UNHSP), the number of slum households in developing countries continues to grow by a higher proportion as compared to its encompassing city. Traditionally, policy makers have concentrated on population control strategies by focussing on birth rates and rural–urban migration to stem the growth and emergence of slums. However, these strategies have often failed to achieve the desired results. In the present paper we find the key underlying processes that explains the observed differences in household life cycle between slum and non-slum households. We find that the slum households when compared to nonslum urban households, exhibit a large variation in the household size over the course of their life cycle, which in turn leads to inefficiency while building slum resettlement colonies. We have developed an agent based model, namely DynaSlum, to identify the key social determinants that impact the behaviour of a slum household. We use a novel and unique dataset based on the field work from 37 slums in Bangalore combined with the NFHS data to calibrate DynaSlum and validate our findings. This paper presents two major insights to address the challenges. First, we find that high rate of home leaving among young adults is the key determinants for the large variation in the life cycle of slum households. Second, we show that reducing home leaving among young adults will reduce the formation number of new slum households and contribute to a higher but stable household size. This will lead to efficiency and higher per capita resource consumption when building capacity for slum development (resettlement colonies) as policy makers would be able to plan for a stable household size. Highlights: We show that household life cycle (HLC) of slums is different from non-slum urban households. We develop and ABM using novel data to model HLC. Model can reproduce the population dynamics of slums in Bangalore. We show that reducing home leaving among young adults reduces the formation of new smaller slumhouseholds. We show that a stable HLC will lead to efficiency and higher per capita resource consumption.